Awareness On Light Pollution Among Teacher Educators - P. Janardhana Kumar Reddy; G. Thirumoorthy; A. Arun; Shahzad Ramadan Hasan (Universitas PGRI Madiun, 2023)
This article is intended to assess the awareness of light pollution among teacher educators. The data were collected from Teacher educators who are working in teacher education institutions under Tamil Nadu Teacher Education University (TNTEU). The self-made multiple-choice Questionnaire was used to collect the data. Both inferential and descriptive statistics were used to analyse the data. There are many interesting findings were derived. The present study created an insight and enlightened about the light pollution among teacher educators